Pemahaman Siswa Terhadap Penyimpangan Perilaku Seksual Dikalangan Remaja SMK - Yora Chantika; Linda Fitria; Rini Sefriani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
In problematic adolescents who are controlled by aggressive and antagonistic urges, the sensitivity to the effects of deviant sexual behavior will generally be higher. Adolescents of this type will channel their curiosity about sex through reading "stencil publications" among their teenage friends, watching blue films, and conducting sexual experiments by masturbating with teenage friends, trying sexual relations with the opposite sex, even with sex workers. attempting homosexual sexual behavior with peers or with transgender women who work as prostitution, committing rape with friends against victims they meet on the street. The adolescent's behavior is a negative sexual attitude characterized by psycho-sociosexual behavior. This study aims to reveal students' understanding of sexual deviance behavior among adolescents. This type of research is a case study qualitative research, while the approach used is descriptive qualitative, which will be described according to the data obtained in the field. Phenomena that occur to students regarding sexual deviance behavior among adolescents. The subjects in this study were 5 people. The results of the study showed that students understood sexual deviance behavior among adolescents. Based on the results of the study, there were negative impacts from sexual deviant behavior, such as free sex, LGBT, while the positive impact was that the subject understood about sexual deviant behavior and the impact of sexual deviance.